Artistic bridge design a systematic treatise on the design of modern bridges according to aesthetic principles - Tyrrell, H. G. 1867-1948 (Myron C. Clark, 1912)
Arguing that a lack of artistic treatment is the greatest fault of American bridges, the author presents many illustrations and guidance on how to improve a bridge's aesthetic appeal.